MENINGKATKAN PERKEMBANGAN KOGNITIF MELALUI KEGIATAN MIND MAPPING - Yurike Dwi Arimbi; Sri Saparahayuningsih; Mona Ardina (Jurnal Ilmiah POTENSIA, 2018)
The problem in this research was whether through mind mapping activity can improve cognitive development on Group B2 of PAUD (Early Childhood Education) IT Ulul Albaab of Bengkulu. The aim of this classroom action research was to improve cognitive development through mind mapping activity on Group B2 of PAUD IT Ulul Albaab of Bengkulu. This was a classroom action research (CAR). In this research it was proven that through mind mapping activity can improve students’ cognitive development. It was proven from the average result of students’ cognitive development on cycle I reached the mean score of 3.70 with classical mastery of 74% which categorized as Good criteria, then on cycle II the mean score reached 4.27 with classical mastery of 85.4% which classified into Good criteria. The suggestion for teacher was to implement mind mapping activity to improve students’ cognitive development. Key words: Cognitive Development, Mind Mapping.